A comparative study of the effectiveness and safety of pregabalin and duloxetine in the treatment of chemotherapy-induced neuropathic pain - Yogendra Singhal; Surendra Kumar Pingoliya; Ashwin Mathur; Parmanand Atal (Palliative Medicine in Practice)
BACKGROUND: Chemotherapeutic medicines are among the several medication types that can cause peripheral neuropathy, a serious disorder marked by symmetrical, distal damage to the peripheral nerves. Chemotherapy-induced peripheral neuropathy (CIPN) is a significant problem that is becoming more prevalent as oncological treatments that use potentially neurotoxic chemotherapy improve the prognosis and cure of cancer. CIPN can need dose decrease or discontinuance, which can have an adverse effect on survival. Relieving the patient from CIPN is required because it enhances their quality of life as well as their mental and physical health. PATIENTS AND METHODS: The patients who were diagnosed with chemotherapy-induced neuropathic pain were randomized into two groups after obtaining written informed consent. Group D received duloxetine 30 mg orally daily in the 1st week followed by 30 mg twice daily until 3 weeks and Group P received pregabalin 75 mg orally daily in the 1st week followed by 75 mg twice daily until 3 weeks. The intensity of pain was measured using the NRS (Numerical Rating Scale) and the DN4 questionnaire was used to evaluate the neuropathic component. Changes in pain score and neuropathic component were assessed at baseline and then at the 2nd and 4th week of follow-up. Data was collected and analyzed using SPSS 20.0 software at a level of significance p < 0.05. RESULTS: At baseline, the mean ± standard deviation (SD) of the NRS score in Group D was 7.12 ± 0.89; in Group P was 7.01 ± 0.66 at the end of the study 4th week, the mean ± SD of the NRS score in Group D was 4.04 ± 0.98; in Group P was 5.18 ± 0.64. At baseline, the mean ± SD of the DN4 score in Group D was 7.21 ± 0.80; in Group P was 6.93 ± 0.85 at the end of the study 4th week, the mean ± SD of the DN4 score in Group D was 4.73 ± 0.42; in Group P was 5.13 ± 0.82. The reduction in NRS scores and DN4 scores at the end of the study (4th weeks) when compared to baseline scores were statistically significant in each group (p < 0.0001). CONCLUSIONS: Both pregabalin and duloxetine are effective in improving the CIPN in patients with cancers. Both the drugs were well tolerated with mild side effects like headache, drowsiness, and sedation. However, duloxetine was found to be more favorable with fewer side effects than pregabalin.